Developing computer adventure education games on mobile devices for conducting cooperative problem-solving activities. (1st January 2013) - Hsu, Yu-Jen; Shih, Ju-Ling
This paper presents the design and evaluation of two digital games that were developed as virtual adventure education activities. College students were invited to participate in the research. Everyone has a mobile device that was networked to solve the multiplayer tasks. The gaming processes were recorded by the game system and human observations, questionnaires and interviews were also conducted to collect qualitative data. The results showed that students either participated in the adventure education activities in physical form, digital form, or mixed form, all reached significant differences on their improvements of group cooperation behaviours and problem-solving abilities. It was evident that the cooperative digital games supported by mobile devices can function as effectively as multiplayer physical games.